Growth and investment dynamics in Germany after the global financial crisis - Georg Erber; Harald Hagemann (DIW Economic Bulletin, 2013)
The German economy recovered more rapidly than the majority of other developed countries from the severe slump that the global economic and financial crisis brought in its wake. Weak demand in the euro area was offset by robust growth in exports to countries outside the region. The German economy's strong competitive position on global markets, particularly on the dynamic emerging and developing markets, played a vital role here. In contrast, over the last decade, the euro area's crisis countries in particular have experienced a decline in their competitiveness on international markets. Due to their dependence on the single European market and failure to focus on innovative products in demand on global markets, they are among the losers in the global competition for foreign direct investment. The reforms that have been introduced will not be able to generate an immediate trend reversal. Even Germany will struggle to maintain its favorable market position as global structural change and competition to attract business to the region are likely to increase in intensity.
Keywords: F14; F15; F43; 330; Germany; innovation; growth; investment